Efektivitas Metode PNF dan Pemberian Shoulder Support Terhadap Perbaikan Pola Gerak dan Stabilitas Persendian Shoulder pada Penderita Post Stroke - Riani baiduri siregar; Heri saputra; Rudi Purwana; Ani Ramadhani (Lembaga Pengembangan Kinerja Dosen, 2026)
Infant motor development is a stage of motor development appropriate to a baby's age and principles. If the basic motor stages are not completed, the baby lacks basic motor concepts, resulting in a lack of awareness of functional movement. Limited motor time, excessive parental supervision, and insufficient motivation and stimulation can lead to delays. Tummy time is one form of stimulation that can be provided to enhance infant development. The benefits of tummy time in improving infant motor development include prone or back positions, rolling, and crawling. This Community Service (PKM) activity was conducted in the physioroom clinic with 15 mothers of babies aged 3-6 months participating. The PkM included outreach, demonstrations, discussions, and a question-and-answer session. Mothers' knowledge of tummy time was determined using pre- and post-tests. The PkM results showed that tummy time can influence infant motor development, with average pre- and post-test scores of 6.4 and 8.6, respectively. This demonstrates that this PkM activity successfully increased mothers' knowledge about tummy time and infant motor development. Keywords: Mother, Baby, Motor Skills, Tummy Time.)